MARILYN CHIN’S REVENGE OF THE MOONCAKE VIXEN AS TEXTUAL SYSTEMIC DESIRING MACHINE - Lestari Manggong; Anton Kurmelev (Metahumaniora, 2023)
Marilyn Chin’s one and only novel, Revenge of the Mooncake Vixen (2009), presents highly fragmented narratives that revolve around the lives of three female Chinese Americans of two different generations in the process of reaching their immigrant American dreams. Such narrative characteristics prompt an analysis conducted in this article which parallels the series of maneuvers of the trio with Deleuze & Guattari’s systemic procedure of coup et flux (cut and flow). The aim is to show that the idea of assimilating American dream with the immigrant’s is a complex matter as it involves series of actions that compromise the two. The trio’s mode of action, the presence of textual divine intervention in the narrative fragments, and epigraphs from classical to popular texts encourage an analysis using narrative studies, focusing mainly on plot structure. In the context of negotiating Chinese American culture, this article argues that within the frame of tale of revenge, the process of reaching the immigrant American dream undergoes a series of endless systemic procedure of coup et flux. The negotiation process presented via uncertainty and series of transits in the novel thus causes endlessness that leads to an idea that the dream, the happiness, would never actually reach its definite ending point; it is merely a series of transits.